Pendampingan Pembuatan E-Newsletter Untuk Menarik Minat Calon Donatur Berdonasi di Panti Asuhan Harapan Remaja Jakarta - Maharani Imran (Institut Ilmu Sosial dan Manajemen Stiami, 2022)
The development of technology during the Industrial Revolution 4.0 has created a modern way of communication between social institutions and potential donors. Potential donors have communication tools connected to the Internet and search for information about orphanages through digital communication channels. The goal of this non-profit activity is to help orphanage managers create E-Newsletter s to increase potential donors' interest in making a donation. The method used is to have lecturer and students assist in the creation of E-Newsletter s. This activity went well and succeeded in publishing an interesting and informative E-Newsletter for the public and potential donors. The suggestion of this community service activity is that orphanage managers can continue to publish E-Newsletter s in collaboration with children of the orphanage to be distributed on websites and other social media.